2014
DOI: 10.1021/ml5003458
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Antituberculosis Activity of 1,3-Benzothiazinone Sulfoxide and Sulfone Derived from BTZ043

Abstract: The discovery of 1,3-benzothiazin-4-ones (BTZs), especially BTZ043 and PBTZ-169 as potent agents for the treatment of tuberculosis, prompted intensive research related to development of potential antituberculosis agents based on electron deficient nitroaromatic scaffolds. Herein we report the syntheses, computational and NMR studies and anti-TB activity of oxidation products, 1,3-benzothiazinone sulfoxide (BTZ-SO) and 1,3-benzothiazinone sulfone (BTZ-SO2) derived from BTZ043. The combined computational and NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…51, 52 BTZ043 exhibits high antimycobacterial selectivity, with no activity observed against representative Gram-positive ( S. aureus and Micrococcus luteus ) and Gram-negative ( P. aeruginosa and A. baumannii) strains. 53 Another class of DprE1 inhibitors is the 1,4-azaindole class, which unlike the benzothiazones, inhibit DprE1 via a non-covalent mechanism. The lead compounds from this series, 8 and 9 exhibit in vivo efficacy in both acute and chronic mouse TB models.…”
Section: Identification Of Narrow-spectrum Antibacterial Agentsmentioning
confidence: 99%
“…51, 52 BTZ043 exhibits high antimycobacterial selectivity, with no activity observed against representative Gram-positive ( S. aureus and Micrococcus luteus ) and Gram-negative ( P. aeruginosa and A. baumannii) strains. 53 Another class of DprE1 inhibitors is the 1,4-azaindole class, which unlike the benzothiazones, inhibit DprE1 via a non-covalent mechanism. The lead compounds from this series, 8 and 9 exhibit in vivo efficacy in both acute and chronic mouse TB models.…”
Section: Identification Of Narrow-spectrum Antibacterial Agentsmentioning
confidence: 99%
“…[2] <INSERT FIGURE 1 HERE> The structure-activity relationship (SAR) and mechanistic studies of BTZs suggest that the NO 2 group at position 8 and the sulfur atom at position 1 are critical for activity, that the -CF 3 at position 6 plays an important role in maintaining activity. [7,[13][14][15][16][17][18][19][20] In our previous study, we focused on the modification at position 2, some of the resulting compounds were found to have improved activity and pharmacokinetic properties. [11,12] Among them, IMB-ZR-1 with the piperidine ring displayed potent in vitro anti-TB activity against the tested MDR-TB strains (MIC = 0.016 ”g/mL).…”
Section: Manuscript a Cmentioning
confidence: 99%
“…A series of potential DprE1 covalent inhibitors with modification on the 2 position of BTZs represented as compounds 1a and 2a was reported (Figure 1) [14][15][16][17]. Interestingly, two compounds with relatively minor modifications to the BTZs core, benzothiazinethione (SKLB-TB1001, 3) and sulfoxide of 1 (BTZ-SO, 4), maintain potent antimycobacterial activities (Figure 1) [18,19]. The crystal structures of the DprE1 with 1 and DprE1 with 2 complex as well as the structure-activity relationships (SARs) of this series indicated that the key constituents for potent activity are the sulfur atom and carbonyl group in the thiazinone ring, a strong electron withdrawing group (CF3, CN, NO2, etc.)…”
Section: Introductionmentioning
confidence: 99%